Breast reconstruction with TRAM: abdominal tomographic evaluation - Igor Moura Soares; Armando dos Santos Cunha; Saulo Francisco de Assis Gomes; Vírginia Gutmacher Galvão Bueno Wadhy Rebehy; Marcela Santos Vilela; Eduardo Natal Batista (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: The transverse rectus abdominis muscle flap (TRAM) is a method of breast reconstruction with good aesthetic results and does not require the use of silicone implants for better body contouring. It was originally described by Holmstrom in 1979 as an ellipse of skin and fat based on an isolated muscle on its vascular pedicle. The systematic reconstruction of the wall defect installed after flap transposition using polypropylene mesh was described in a previous study by Cunha. The article aims to evaluate changes in the abdominal wall, after the systematization of polypropylene mesh placement during TRAM reconstruction surgery. Method: This is a retrospective cohort study that evaluates possible changes in the abdominal wall of patients undergoing the TRAM flap with preand postoperative abdominal computed tomography. Results: A reduction in the size of the abdominal cavity of, on average, 14.5% and 14.2% in the thickness of the abdominal wall subjected to TRAM was evidenced. The greatest reduction in abdominal wall thickness was in a patient who underwent a bipedicled flap, with 50.7%. The complications presented were umbilical hernia, late seroma, perithellal fibrosis, and thread granuloma. Conclusion: In this study, tomography after surgery demonstrated a reduction in the volume of the abdominal cavity and thickness of the abdominal wall, which did not statistically influence the appearance of abdominal hernia, bulging, mesh extrusion, or other deformities.